Atomic force microscopy: more than surface imaging - Bishop, Terrance Tyler, author; Krapf, Diego, advisor; Prasad, Ashok, committee member; Van Orden, Alan, committee member (Colorado State University. Libraries, 2020)
Atomic Force Microscopy (AFM) is a powerful imaging tool that has capabilities that go beyond the abilities of most other microscopes. Here, three examples of these capabilities were considered. First, the AFM was operated in an image generating mode to determine the surface heterogeneity of polysaccharide membranes. Second, the AFM was used to record force-indentation curves, these curves were fit with a Hertzian model to determine the stiffness of murine smooth muscle cells. Finally a approach for attaching 10 µm and 2 µm polystyrene beads to tip-less AFM cantilevers was proposed, and a viscoelastic contact model was tested to determine the viability of the created probes.
Keywords: colloidal; Hertzian; atomic; microscopy; force